The Friendshipâ€™s Values in Teenlit Dealova, Rahasia Bintang and Tetralogy â€œKosan Sodaâ€ by Dyan Nuranindya (Universitas Negeri Semarang, 2019)
The novel by Dyan Nuranindya namely Dealova, Rahasia Bintang and Tetralogy